STRATEGI GURU DALAM MENINGKATKAN KOSAKATA BERBAHASA ANAK TUNAGRAHITA MELALUI PEMBELAJARAN MENCOCOKKAN GAMBAR DI SLB C MUSDALIFAH - Alifia Nur Rahma; Yusmita Kusumaningsih; Sabrina Patuzahra; Rika Widya; Mhd Iqbal (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
Children with special needs are children who have unique characteristics that differentiate them from their peers. One form of this is children with intellectual disabilities or mental retardation, who are terminologically referred to as children with intellectual disabilities. The purpose of this study is to identify teachers' strategies in improving the vocabulary of children with intellectual disabilities through picture-matching learning, the obstacles encountered in the learning process, and to understand students' responses to the picture-matching method. This study uses a qualitative approach, focusing on inductive analysis of thought processes. The results of this research show that visual learning strategies using the picture-matching method can help children with intellectual disabilities to remember new vocabulary by looking at pictures. Picture media is a teaching technique that utilizes images/photos to convey messages to students. It is expected that through images/photos, students will find it easier to develop ideas/thoughts in written form.